The Suitability of Helen Joseph Armstrong’s Raglan Sleeve Pattern for Idealized Body Types of Indonesian Women - Fithri, Aulya; Nelmira, Weni (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The Helen Joseph Armstrong raglan sleeve pattern is widely used in garment making, but it is not yet fully suitable for the body proportions of ideal adult Indonesian women. This misfit can result in discomfort and aesthetic issues in clothing, which necessitates research to analyze the weaknesses and make pattern adjustments. This study aims to identify weaknesses, make improvements, and evaluate the fit of the raglan sleeve pattern for women with a height of 165 cm and weight of 53 kg, in accordance with the Body Mass Index (BMI) classification for adult Asians. The research method uses an applied approach, with a Likert scale-based assessment format and descriptive statistical analysis. The evaluation focuses on indicators such as sleeve length, peak arm height, midline of the arm, shoulder slope, raglan line, bicep, elbow line, and sleeve cuff circumference by four panelists. The results show that in the first fitting, the average pattern fit was only 63%, categorized as fairly suitable. Several weaknesses were identified, such as a backward shoulder line, raised raglan line, and overly large biceps. Adjustments were made by modifying the shoulder line, lowering the raglan line, reducing bicep size, and adjusting the sleeve cuff circumference. In the second fitting, the pattern fit increased to 86%, categorized as very high. These results indicate that pattern adjustments are essential to achieving optimal fit for ideal adult Indonesian women, thereby improving both comfort and aesthetic appearance in clothing.